Overview of software editors based on automatic control system - Sadykova Жанна; Zhumabaev Атағали; Artykbaev Алмас (Рroblems of engineering and professional education, 2023)
This article analyzed the similarities and differences between AutoCAD, Solid Works and ArchiCAD programs based on a computer-aided design system. And also considered graphic software editors with two-dimensional geometric capabilities and three-dimensional modeling. Applications of software editors and their directions are listed and disclosed.